Understanding the Cultural Politics Experience of Indonesian Male Domestic Helpers in Malaysia - Abadi, Mansurni; Wulandari; Nur Pratiwi, Nia (Jurnal Partisipatoris, 2024)
This research explores the cultural-politics dynamics of Indonesian male domestic workers in Malaysia as they confront and challenge societal prejudices while taking on fatherhood-associated responsibilities. It delves into the obstacles these men face due to ingrained gender stereotypes that question their suitability for domestic roles, particularly in a foreign cultural context. The primary objective is to understand how these men redefine their identities and assert their roles as nurturers and providers, challenging traditional masculine ideals. This study uses a qualitative research design and a narrativization approach to explore the experiences of Indonesian male domestic helpers. Through in-depth interviews and personal narratives, the research reveals how these men navigate their roles as caregivers and fathers, challenging traditional gender norms and gaining recognition within their households and communities. The study also highlights the importance of upholding cultural ties and personal resilience in their experiences as migrant domestic workers.